Recentralization in China? - Ahmad, Ehtisham; Keping, Li.; Richardson, Thomas; Singh, Raju. (Washington, D.C. : International Monetary Fund, 2002)
The paper assesses the changing nature of the relations between the provinces and the central government in China during the 1990s. It examines the fiscal reforms initiated in 1994 and subsequent developments. The expenditure needs of the center and the richer provinces are juxtaposed against the need for "redistribution" to the more backward regions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet